A Survey of Attack Mechanisms on Infrastructure-Mode 802.11 Wireless Networks and Their Detection - Encyclopedia of Information Science and Technology, Third Edition [Book] (2014)
The 802.11 wireless network revolution has not come without trouble. Since their creation, wireless networks have been plagued with security problems, derived from poor initial design of 802.11 security mechanisms, accelerated deployment and adoption of the technology, and lack of user education.